2021
DOI: 10.1088/1748-605x/ac0451
|View full text |Cite
|
Sign up to set email alerts
|

Optimized alginate-based 3D printed scaffolds as a model of patient derived breast cancer microenvironments in drug discovery

Abstract: The cancer microenvironment influences tumor progression and metastasis and is pivotal to consider when designing in vivo-like cancer models. Current preclinical testing platforms for cancer drug development are mainly limited to 2D cell culture systems that poorly mimic physiological environments and traditional, low throughput animal models. The aim of this work was to produce a tunable testing platform based on 3D printed scaffolds (3DPS) with a simple geometry that, by extracellular components and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…In the previous studies using BC cell lines and mainly 3D spheroid bioprinting, the authors described the growth characteristics, size and shape distribution [67] of the spheroids (live/dead cell ratio measured by different assays) and analysed some protein expressions (MMPs, EMT markers, stem cell markers, integrins, cell-cell connections, and matrix depositions) [58,[68][69][70] or certain drug sensitivities (e.g., doxorubicin, paclitaxel, and 5-FU). In the case of doxorubicin treatment, maintained or decreased sensitivity were documented in 3D culture conditions [36,37,49,60,[69][70][71][72]. These contradictions can be explained by the limitations of the used proliferation/viability assays, cell types and the differences between the used cell line and 3D culturing techniques in previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous studies using BC cell lines and mainly 3D spheroid bioprinting, the authors described the growth characteristics, size and shape distribution [67] of the spheroids (live/dead cell ratio measured by different assays) and analysed some protein expressions (MMPs, EMT markers, stem cell markers, integrins, cell-cell connections, and matrix depositions) [58,[68][69][70] or certain drug sensitivities (e.g., doxorubicin, paclitaxel, and 5-FU). In the case of doxorubicin treatment, maintained or decreased sensitivity were documented in 3D culture conditions [36,37,49,60,[69][70][71][72]. These contradictions can be explained by the limitations of the used proliferation/viability assays, cell types and the differences between the used cell line and 3D culturing techniques in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…In the presented study, we tested a 3D bioprinted in vitro model of the luminal BC cell line (ZR75.1). Using the previously selected alginate-based bioinks, which were compatible for bioprinting several BC cells [36,37], we constructed ZR75.1 tissue-mimetic scaffolds (TMSs) combining scaffolds and cell-containing bioink layers, and incubated these structures for a minimum of 3 days. In these conditions, the growing and survival capacities of the printed TMSs were tested by proliferation and viability tests at different time points.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by differences in cell polarity, where integrins are required for maintaining cell polarity ( Lee and Streuli, 2014 ) and where 2D cultured cells are known to be highly polar in comparison to 3D cultured cells ( Baker and Chen, 2012 ). In addition, ABCG2, a marker for cancer stemness that is related to cancer drug resistence and shown to be upregulated upon doxorubucin treatment in a 3D environment, ( Svanström et al, 2021 ) and was downregulated in a 3D environment. ABCG2 expression is controlled by several different transcriptional factors, including ESR1 ( Mo and Zhang, 2012 ) which here was downregulated on the protein level in 3D relative 2D cultured cells, supporting a downregulation of ABCG2 .…”
Section: Discussionmentioning
confidence: 99%
“…Alginate (Protanal LF 10/60, FMC) with hydroxyapatite (Sigma-Aldrich) was prepared and printed as described in a study by Svanström et al (2021) . In brief, 8% (v/v) alginate and 5% (w/v) hydroxyapatite were mixed using an Ultra-Turrax T50 digital dispenser (IKA), and printed in 4 layer discs ⌀20 mm using an EnvisionTEC 4th Gen 3D-Bioplotter ® (EnvisionTEC) and a needle diameter of 400 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported a reduced susceptibility to treatment with camphotectin or paclitaxel compared to unsorted MCF7 cells, confirming the viability of the testing system. Alginate bioprinted scaffolds containing periostin and hydroxyapatite were shown to induce gene expression changes in MCF7 and MDA-MB-231 cells, upregulating the marker genes for stemness (CD44, ETV1, MALAT1), epithelial-mesenchymal transition (TWIST1, SNAI1, MUC1), and downregulating the markers of cell proliferation (MKI67, CCNA2) and differentiation (EPCAM) relative to 2D culture [83]. Additionally, the transcriptomic pattern of response to doxorubicin and 5-fluorouracil differed between the cells cultured in 3D versus 2D.…”
Section: Breast Cancermentioning
confidence: 99%